Hyaluronic Acid as a Carrier Supports the Effects of Glucocorticoids and Diminishes the Cytotoxic Effects of Local Anesthetics in Human Articular Chondrocytes In Vitro - Lukas B. Moser (MDPI AG, 2021)
The current study aimed to investigate the cytotoxicity of co-administrating local anesthetics (LA) with glucocorticoids (GC) and hyaluronic acid (HA) in vitro. Human articular cartilage was obtained from five patients undergoing total knee arthroplasty. Chondrocytes were isolated, expanded, and seeded in 24-well plates for experimental testing. LA (lidocaine, bupivacaine, ropivacaine) were administered separately and co-administered with the following substances: GC, HA, and GC/HA. Viability was confirmed by microscopic images, flow cytometry, metabolic activity, and live/dead assay. The addition of HA and GC/HA resulted in enhanced attachment and branched appearance of the chondrocytes compared to LA and LA/GC. Metabolic activity was better in all LA co-administered with HA and GC/HA than with GC and only LA. Flow cytometry revealed the lowest cell viability in lidocaine and the highest cell viability in ropivacaine. This finding was also confirmed by live/dead assay. In conclusion, HA supports the effect of GC and reduces chondrotoxic effects of LA in vitro. Thereby, the co-administration of HA to LA and GC offers an alternative less chondrotoxic approach for treating patients with symptomatic osteoarthritis of the knee.